Effect of biocontrol agents, fungicides and plant extracts on sclerotial viability of Sclerotinia sclerotiorum * - SHARMA, B K; BASANDRAI, ASHWANI K (The Indian Journal of Agricultural Sciences, 2013)
Â Â